Essential Speech and Language Technology for Dutch: Results by the STEVIN-programme - Peter Spyns, Jan Odijk (Theory and Applications of Natural Language Processing, 2013)
Computational Linguistics; Germanic Languages; Artificial Intelligence (incl. Robotics); Computing Methodologies